Engineered drug-loaded cellular membrane nanovesicles for efficient treatment of postsurgical cancer recurrence and metastasis - Yu, Yongkang (2023)
Cancer recurrence and metastasis are still common causes of postsurgery death in patients with solid tumors, suggesting that additional consolidation therapeutic strategies are necessary. We have previously found that oxaliplatin (OXA) treatment causes further up-regulation of CD155, which is abundantly expressed in tumors for resulting in increased sensitivity of cancer to anti-CD155 therapy. Here, we report O-TPNVs, which are TIGIT-expressing cell membrane and platelet cell membrane fusion nanovesicles (TPNVs) loaded with OXA. Platelet-derived membrane components enable O-TPNVs to target postsurgery wounds and interact with circulating tumor cells (CTCs). OXA directly kills residual tumor cells and CTCs, induces immunogenic cell death, and activates the immune system. TPNVs bind to CD155 on tumor cells, block the CD155/TIGIT pathway, and restore CD8+ T cell activity. In vivo analyses reveal that O-TPNVs achieve synergistic chemotherapeutic and immunotherapeutic effects, effectively inhibiting the recurrence and metastasis of triple-negative breast cancer (4T1) after surgery.